THE IMPLEMENTATION OF CROWDSOURCING IN A VEHICLE RESCUE STARTUP - Kiding, Patrick; Lemantara, Julianto; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
As time goes by, number of vehicles are greatly increase. The vehicle users will be in a difficult situation to find assistance with the location of the nearest repair shop if something happened to their vehicle. Human are social creatures. This concept is the basis for the development of the crowdsourcing concept. The combination of the internet and the crowdsourcing concept can be a powerful resource in getting a job done. Over time, vehicle users become lazy about maintaining vehicle performance. They assume that the vehicle is still fit for use. This assumption is will causes more damage to the vehicle. This condition has a business opportunity by seeing the increase in the number of vehicle and the demand for routine vehicle service. Based on these problems, a start-up using the crowdsourcing concept is proposed which helps the community in providing and seeking assistance as well as the location of the nearest workshop as well as helping the nearest workshop to get business opportunities. Based on the results of testing the application can bridge the fulfillment of the needs of service users and service providers, so it can be concluded that the application is functioning properly.